THE INFLUENCE OF TEACHER FACTORS IN TEACHING ENGLISH AT SMA XAVERIUS LUBUKLINGGAU - Janneta Palingga (Journal of English Education, Literature and Linguistics, 2019)
The problem of this reasearch were what is the teachers factors and how the teachers’ factors in infuencing successfulness on English teaching learning of SMA Xaverius Lubuklinggau. This research was Descriptive qualitative. The subjects of this research were the English teachers of tenth, eleventh, and twelfth grade in SMA Xaverius Lubuklinggau. Observation, and Interview were used. In observations, this research used observation sheet which consist of 2 aspects with 24 indicators, and Field notes. For interview it was consisted of 13 questions from 2 aspects. In analyzing the data, case study is applied and obtained the research by adjusting the fieldnotes then crosscheck the data from voice recorder when as the result of interviewing the subject and the data checklist of observation sheet. The teachers factors in teaching English is : teacher should be able to manage their classroom, because good vibes in classroom can help the english teacher to conduct their teaching process, then a teacher should have good skills in mastering English for making good comprehension, a nice teacher should memorize students’ name, smile often, giving motivation, and doing assessment. There were 2 factors in influencing the successfulness on English teaching learning as the characteristics of teacher there were ; skills and qualifications means should have good comprehension about practical knoeledge, content knowledge, contextual knowledge, and pedagogical knowledge, then support for the teachers such as ; orientation, adequate material, course guides, division of responsibilities, futher training, teaching release, mentors, feedback, rewards, help lines, and review. There are factors that influencing English Teaching Learning ; Institusional Factors, Teacher Factors, Teacher Factors, Teaching Factors, and Learners Factors which can be inspiration to the next researcher to conduct and expand new research.